Exploring the use of social media as a digital study guide - Shemberger, Melony; Wright, Leigh (Journal of Interdisciplinary Studies in Education, 2019)
The purpose of this case study was to understand how students could study forcourse examinations using social media. This study used two theoreticalframeworks, Web 2.0 Technologies and connectivism, as the guiding concepts toexplore how students in an introductory college course perceived the use ofTwitter and Storify as test reviews and study guides. Forty-six university studentsin a journalism course were surveyed about their perceptions of theseapproaches. Results showed students believed the Twitter in-class review helpedthem to recall information more effectively. In addition, students used Storify asa study guide, and most said Storify helped to improve their test grades.Recommendations to modify this pedagogical approach and future research ideasare discussed.